Career Development and Employee Performance in Private University : a Study of UNTAG Semarang, Central Java, Indonesia - Suparjo Suparjo; Nurchayati Nurchayati (Universitas 17 Agustus 1945 Semarang, 2023)
This study was an attempt to explore the nexus between career development and employee job performance in UNTAG Semarang, Central Java, Indonesia. The study was necessitated following the need to institute career development programs in organizations for employees to acquire additional knowledge for improved job performance. This study was a survey-type of research that employed a correlational design in an attempt to ascertain the magnitude of the relationship between the studied variables. Structured questionnaires were administered to a sample size of 250 drawn from the population of the study. The Likert 5- point scale was used in quantifying responses while simple regression was employed in determining the degree of the relationship between career development and employee job performance. The result shows a strong relationship between career mentoring and the quality of employee job performance in the organization and concludes that organizations that wish to improve on employee job performance must institute and entrench career mentoring necessary for skill acquisition. The study recommends that organizations should encourage career counseling activities as a leeway to providing a sustainable framework upon which employees acquire the needed operational skills that will enhance their job performance in a typical organization.